The Handbook of Nanomedicine - Jain, Kewal K.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2017)
Nanomedicine is defined as the application of nanobiotechnology in clinical medicine, which is currently being used to research the pathomechanism of disease, refine molecular diagnostics, and aid in the discovery, development, and delivery of drugs. In The Handbook of Nanomedicine, Third Edition, Prof. Kewal K. Jain updates, reorganizes, and replaces information in the comprehensive second edition in order to capture the most recent advances in this dynamic field. Important components of nanomedicine such as drug delivery via nanobiotechnology and nanopharmaceuticals as well as nanooncology, where the greatest number of advances are occurring, are covered extensively. As this text is aimed at nonmedical scientists, pharmaceutical personnel, as well as physicians, descriptions of the technology involved and other medical terminology are kept as clear and simple as possible. In depth and cutting-edge, The Handbook of Nanomedicine, Third Edition informs its readers of the ever-growing field of nanomedicine, destined to play a significant role in the future of healthcare.
Keywords: Nanotechnology; Biotechnology; Nanotechnology; Biotechnology